Spinoza and medieval Jewish philosophy - Nadler, Steven M. (Cambridge University Press, 2014)
"Over the last two decades there has been an increasing interest in the influence of medieval Jewish thought upon Spinoza's philosophy. The essays in this volume, by Spinoza specialists and leading scholars in the field of medieval Jewish philosophy, consider the various dimensions of the rich, important, but vastly under-studied relationship between Spinoza and earlier Jewish thinkers. It is the first such collection in any language, and together the essays provide a detailed and extensive analysis of how different elements in Spinoza's metaphysics, epistemology, moral philosophy, and political and religious thought relate to the views of his Jewish philosophical forebears, such as Maimonides, Gersonides, Ibn Ezra, Crescas, and others. The topics addressed include the immortality of the soul, the nature of God, the intellectual love of God, moral luck, the nature of happiness, determinism and free will, the interpretation of Scripture, and the politics of religion"--